The Issue of Etiquette in “Avesta” - Saparov Berdiyar Baltabaevich (Penerbit Jurnal Indonesia, 2024)
In addition to being the holy book of zoroastrianism counted from the ancient religions of the world, “Avesta” is important in the study of the centuries - old history, socio-economic life, spirituality and values of our ancestors. In the great spiritual heritage of our ancestors, special attention was paid to the issues of education and spirituality, which indicates that a high culture has existed in our country since ancient times. This article will talk about the ideas put forward in our rich spiritual heritage “Avesta” about etiquette, education, spirituality.